Der deutsche Venture-Capital-Markt – Investitionen und Rahmenbedingungen; German venture capital market: Investments and framework - Seyer Shafie; Matthias Liedtke; Reza Asghari (Wirtschaftsdienst, 2021)
Innovative Start-ups sind aus mehreren Gründen durch ein hohes Risiko gekennzeichnet. Venture Capital (VC) ermöglicht es Start-ups, ihre Ideen zu Innovationen zu entwickeln und senkt das Risiko des Scheiterns. Diese Form der Finanzierung ist ein wesentlicher Bestandteil im globalen Wettbewerb. Der deutsche VC-Markt weist zumindest in der Spätphase der Unterstützung von Start-ups Mängel auf. Gegenüber den USA und China besteht ein erheblicher Aufholbedarf. – – Innovative start-ups are characterised by a high level of risk for several reasons. Venture capital (VC) enables start-ups to develop their ideas into innovations and lowers the risk of failure. This form of financing is an essential component in the global competition. This paper aims at examining the German VC market with regard to its investments and framework conditions. The framework conditions that influence VC transactions are, on one end of the spectrum, the political and regulatory environment and, on the other, the innovation climate such as societal attitudes towards entrepreneurial and opportunity risk. The paper concludes with some important policy implications.
Keywords: G24; L26; M13; 330; Risikokapital; Deutschland